Monitor application of multi-electrochemical sensor in extracting bromine from seawater. Issue 12 (4th December 2019) - Wang, Qiujin; Wu, Jianbo; Zhao, Guochen; Huang, Yuanfeng; Wang, Zhen; Zheng, Hao; Zhou, Yifan; Ye, Ying; Ghomashchi, Reza
Abstract : In this paper, a set of online measurement devices of multi-electrochemical sensor was investigated. Combined with industrial distributed control system, it was first applied in extracting bromine from seawater to realize the real-time adjustment of production process parameters. In the process of extracting bromine from seawater, the pH value of acidified raw brine, the addition amount of Cl2 in the oxidation stage and the addition amount of SO2 in the absorption stage are key parameters to control the whole production process. The multi-electrochemical sensor realized a rapid and high-throughput detection of the above parameters by integrating an all-solid-stage bromide ion selective electrode (Br-ISE), Eh electrode and pH electrode. The Br-ISE and the pH electrode were self-developed electrodes and the Pt electrode was Eh electrode. The pH electrode was used to control the addition amount of H2 SO4 during the acidification of the brine. The Eh electrode was used to control the addition amount of Cl2 during the oxidation stage and the addition amount of SO2 during the absorption stage. The Br-ISE was used to monitor the Br − concentration change in the raw brine. Results showed the optimum range of Eh in the oxidation stage and absorption stage of brine were 950–1000 mV and 580–610 mV, respectively. The application of multi-electrochemical sensor in industrial bromine production can realize real-time control of material addition and save the cost of production.